In pursuit of food system integrity: the situational prevention of food fraud enterprise - Lord, Nicholas (European journal on criminal policy and research, 2017)
There is much talk surrounding food fraud policy, and while there is convergence around the need to ‘do something about it’, there can be divergence around how this should be done as seen in the decisions and actions of concerned stakeholders. However, underpinning the policy agendas in relation to food fraud there is an aim to prevent (or at least reduce) food fraud, crime and harms, to improve the integrity of the food system. This article develops a mode of analysis that integrates ‘enterprise theory’ with ‘situational prevention theory’ to develop an understanding of how food frauds are situated actions, shaped by contingent enterprise conditions that influence how food frauds are organised and why decisions to offend become rational. We apply this integrated framework to the Spanish olive oil market. Drawing on data collected on market conditions and case study analyses of particular frauds to better understand the situated nature of food frauds we suggest mechanisms that could be used to prevent fraud in particular situations under these conditions. We conclude that this mode of thinking and analysis can be applied to a range of frauds across different food networks.